Title- Analysis of the Impact of the Human Resource Service Quality of ARAMAX on the Customer Satisfaction and Loyalty in GCC - SOLANKI, KALPANA (Archives of Business Research, 2022)
The purpose of this research is to study the human resource service quality of Aramex, and to show how the service quality and responsiveness affects customer satisfaction, loyalty, and success in the delivery industry and to see if Aramex meets the expectations of their customers. The delivery industry has changed dramatically over the years. The success of the businesses depends on quality, reliability, service, and price. Companies compete by offering different services that effect customer satisfaction. The technology development also played an important role in international parcel delivery, and improvements to services in the industry. With the development of online shopping, courier industry is in great demand. Individuals and companies sell online and market themselves worldwide. Aramex became a global brand that is known for its advanced products and services. Aramex accessible location between the East and West allows it to reach anywhere it the world delivering customized logistics regionally and globally. Aramex take innovation in technology into consideration as one of the critical elements. The covid 19 pandemic has immensely increased the business of Aramex in 2020-21